2009
DOI: 10.1590/s0004-28032009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de neoplasias/adenomas avançados colorretais no seguimento a longo prazo de pacientes submetidos a colonoscopia com polipectomia

Abstract: RESUMO -Contexto -A colonoscopia e a polipectomia diminuem a incidência do câncer colorretal, assim como a mortalidade dele decorrente. O intervalo efetivo entre os exames de seguimento é determinado por características clínicas e achados endoscópicos considerados como preditivos para o desenvolvimento de lesões neoplásicas colônicas avançadas. Objetivos -Avaliar a taxa de surgimento de lesões neoplásicas avançadas em pacientes submetidos a colonoscopias de seguimento em serviço de referência. INTRODUÇÃOO cân… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Follow-up is essential due to the risk of recurrence (39) . Current guidelines recommend performing control colonoscopies between 3 and 6 months for large polyps undergoing piecemeal resection (53) .…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up is essential due to the risk of recurrence (39) . Current guidelines recommend performing control colonoscopies between 3 and 6 months for large polyps undergoing piecemeal resection (53) .…”
Section: Discussionmentioning
confidence: 99%
“…Colonoscopy is considered the method of choice for this purpose 20 . Randomized clinical trials and several cohort studies have shown that colonoscopic polypectomy reduces its incidence by 76-90%, as compared with a general population registry 22 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The adenoma-carcinoma sequence was fi rst analyzed by Morson and is considered as the main path for colorectal carcinogenesis [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent updates of the National Polyp Study and the U.S. Multi-Society Task Force recommend that patients be identified as low risk (one or two tubular adenomas smaller than 1.0 cm or low grade dysplasia) or high risk (three or more adenomas, one of them being larger than 1.0 cm, villous or tubulovillous histology or high grade dysplasia) 10 . Low risk patients should undergo another colonoscopy in five years or more, while high risk patients should be submitted to a new colonoscopy in three years, as long as all polyps are properly removed 4,10,18 . According to guidelines of the American Gastroenterology Association and the American College of Gastroenterology, low risk patients should be re-evaluated in five years 10 .…”
Section: Vol 31 Nºmentioning
confidence: 99%